Spatially Patterned Gene Delivery for Localized Neuron Survival and Neurite Extension - Houchin-Ray, Tiffany (2007)
Natural tissues can have complex architectures, which arise in part from spatial patterns in gene expression. Regenerative strategies for damaged tissue must recreate these architectures to restore function. In this article, we demonstrate spatially controlled gene delivery from a substrate for directing cellular processes. Non-viral vectors were immobilized to substrates in linear patterns using microfluidic techniques, and cells cultured on the surface had localized gene expression within the cell population. Transfection was achieved in pattern widths as low as 100 µm, with efficiencies dependent on the microchannel treatment and vector concentration. The ability of patterned expression to localize cellular processes was investigated using a neuronal co-culture model. Patterned expression of the diffusible neurotrophic factor nerve growth factor initiated neuron survival and neurite outgrowth primarily within the pattern, which decreased significantly in regions directly adjacent to the pattern. Primary neurite density was significantly greater on patterned substrates than on surfaces without patterns. This approach demonstrates the basic technology to create patterns of gene expression that can direct tissue formation and could be employed in regenerative strategies to recreate the complex cellular architectures observed in tissues.